2018
DOI: 10.1002/hup.2653
|View full text |Cite
|
Sign up to set email alerts
|

Using the Severity of Dependence Scale to screen for DSM‐5 khat use disorder

Abstract: Although khat is a mild stimulant, there is clear evidence that some consumers are both concerned with their use and experience problems associated with their use. Consistent with its application for other drugs, the SDS is a brief and simple screening tool that appears to validly identify individuals experiencing a khat use disorder syndrome and experiencing high rates of adverse consequences in association with use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…The remaining studies employed tools like the modified version of "Alcohol Use Disorder and Associated Disabilities Interview Schedule-IV (AUDA-DIS-IV)" [32], a single Likert scale question with varying points (e.g., 2-point scale, 4-point scales) [33,34], or questions about the age of the onset of chewing [35], and the amount of chewing [36]. Only two studies employed a standardized and khat-specific multi-item module for measuring khat chewing [37,38].…”
Section: Measurement Of Khat Chewing Patternsmentioning
confidence: 99%
“…The remaining studies employed tools like the modified version of "Alcohol Use Disorder and Associated Disabilities Interview Schedule-IV (AUDA-DIS-IV)" [32], a single Likert scale question with varying points (e.g., 2-point scale, 4-point scales) [33,34], or questions about the age of the onset of chewing [35], and the amount of chewing [36]. Only two studies employed a standardized and khat-specific multi-item module for measuring khat chewing [37,38].…”
Section: Measurement Of Khat Chewing Patternsmentioning
confidence: 99%
“…The severity of dependence scale [22] is currently the most widely used measure of problematic khat use, but it only measures a narrow concept of problematic khat use. Thus, taking previous theoretical and methodological lessons, we have developed the Problematic Khat Use Screening Test (PKUST-17) following standardized and rigorous procedures [17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…One study [55] suggested gender by age interaction for problematic khat use. Many of the studies reported that the construct psychological dependence is valid and applicable for problematic khat use [17,21,55,56]. Few studies applied constructs-khat use disorder [16] and harmful khat use [19] to denote problematic khat use.…”
Section: Psychometric Studiesmentioning
confidence: 99%
“…There was a discrepancy in the psychometric properties of SDS. Two studies [17,56] suggested SDS is a unidimensional scale, but another study [55] found 2 factors where items 3 and 4 could be collapsed into one domain desire to stop. Kassim et al [17] recommended ≥6 points cutoff, whereas Duresso et al [56] established ≥3 using DSM-5 stimulant use disorder as a gold standard and ≥5 cutoff for another study [55].…”
Section: Psychometric Studiesmentioning
confidence: 99%